Pendekatan Konseling Dalam Menangani Pecandu Narkoba - Ati Kusmawati; Fahmi Ariansyah Wibowo; Muhammad Nabila Farchan; Muhammad Prihandoko Nur Dirgantara (Concept: Journal of Social Humanities and Education, 2024)
Drugs are an item that is often misused by irresponsible people. From year to year the problem is increasingly widespread. There are many factors that cause people to become infected with drug abuse. Starting from teenagers to adults with different causes and reasons. Basically, everyone who is aware understands that drugs are illegal, there are consequences both from a legal perspective and the impact they will have on the body of the person who uses them. Therefore, optimal roles and high self-awareness are needed from various parties in dealing with this drug problem. In particular, the family's role is very vital in protecting and educating their families about drugs.